Colonial knowledge, invention and reinvention of Malay Identity in pre-independence Malaya: a retrospect - Fernandez , Callistus (Universiti Kebangsaan Malaysia, 1999)
This paper discusses how Malay identity in the pre-colonial era was ruler-centred and specific towards kingdoms of Malaccan descent changed to become a ‘bangsa Melayu’ encompassing all the definitive peoples of Malaya under the name of Malay. The crucial break between an identity which was kerajaan centerd and a larger imagined Malay ethnie came with the introduction and expansion of colonial knowledge. Colonial knowledge in essence and its attributing characteristics. Similarly, the dominant position of colonial knowledge introduced a common history of origin among the Malays, a geographical boundary, the emphasis on Malay special rights and racial politics and the promotion of education and print culture among the Malays. The introduction of these modern gesellschaft feature promoted a sense of unity ‘bangsa’ oriented. This was furter echanced through the struggle for Malaya’s independence.